Analisis Tindak Tutur Direktif Pada Ceramah Ustadz Abdul Somad Edisi Tanya Jawab Kajian Musawarah Bersama Artis Hijrah - Safitri, Alfiyani Nur; Utomo, Asep Purwo Yudi (Institut Agama Islam Negeri (IAIN) Curup, 2020)
The speech basically aims to invite, call, awaken, direct, and guide audiences to act in accordance with the guidance of Islamic teachings so that directive speech acts are often used by Islamic preachers, including those in Ustadz Abdul Somad's lectures. This study aimed to describe: 1) The types of directive speech acts in Ustadz Abdul Somad's speech, the question and answer edition of musawarah studies with hijrah artists; 2) the function of the directive speech acts used in Ustadz Abdul Somad's speech, the question and answer edition of musawarah studies with hijrah artists. This study applied a qualitative descriptive study. The objects of this study were the utterances of Ustadz Abdul Somad's speech, the question and answer edition of musawarahÂ studies with hijrah artists on YouTube. The data were collected using observation and note-taking techniques. The current study found that there were direct speech acts, indirect speech acts, literal speech acts, and non-literal speech acts. Based on the pragmatic function of directive speech acts, directive functions included the functions of asking, questioning, ordering, prohibiting, and advising. The dominant type and function of directive speech acts in Ustadz Abdul Somad's speech referred to directive speech acts with the function of advising